الأمن الغذائي في الجزائر الأبعاد والمؤشرات - حفظ الله، عبد الحكيم; الحمزة ،عبد الحليم (جامعة الوادي University of Eloued, 2024)
The study aimed to estimate the relationship between food security indicators and their determinants in Algeria during the period (1990-2022). The Autoregressive Distributed Lag (ARDL) model was applied to study the cointegration relationship and determine the extent of this relationship. The estimation results revealed that the error correction term was negative and significant at the 5% level, confirming the existence of a long-term equilibrium relationship between the study variables. Through diagnostic tests, it was found that the model is significant and there is no autocorrelation of errors or heteroscedasticity. The analysis results showed a positive relationship between the dependent variable, the food security index, and the explanatory variables, namely the cultivated area, gross domestic product, and wheat production.
Food security in Algeria, dimensions and indicators Standard study during the period (1990-2022)
Keywords: امن غذائي; ابعاد; مؤشرات; Food Security; Indicator; Dimensions